A Comprehensive Paper on Performance Analysis between AODV & DSDV Routing Protocol (International Journal of Engineering and Computer Science, 2014)
Keeping the routing overhead minimal is the key to design an efficient routing protocol for mobile ad hoc network MANET. This type of networks is a non infrastructure, self-configuring and decentralized set of mobile nodes. The node moves at different speeds in independent random form, connected by any number of wireless links, where each node is ready to pass or forward both data and control traffic unrelated to its own use ahead (Routing) to other nodes in a flexible interdependence of wireless communication in between. In contrast to infrastructure wireless networks, where the communication between network nodes is take place by a special node known as an access point. It is also, in contrast to wired networks in which the routing task is performed by special and specific devices called routers and switches. In this paper we compare the performance of AODV & DSDV by two parameter PDR & End to End Delay.